Revisiting the Role of Clathrin-Mediated Endoytosis in Synaptic Vesicle Recycling - Milosevic, Ira (Frontiers in Cellular Neuroscience, 2018)
Without robust mechanisms to efficiently form new synaptic vesicles (SVs), the tens to hundreds of SVs typically present at the neuronal synapse would be rapidly used up, even at modest levels of neuronal activity. SV recycling is thus critical for synaptic physiology and proper function of sensory and nervous systems. Yet, more than four decades after it was originally proposed that the SVs are formed and recycled locally at the presynaptic terminals, the mechanisms of endocytic processes at the synapse are heavily debated. Clathrin-mediated endocytosis, a type of endocytosis that capitalizes on the clathrin coat, a number of adaptor and accessory proteins, and the GTPase dynamin, is well understood, while the contributions of clathrin-independent fast endocytosis, kiss-and-run, bulk endocytosis and ultrafast endocytosis are still being evaluated. This review revisits and summarizes the current knowledge on the SV reformation with a focus on clathrin-mediated endocytosis, and it discusses the modes of SV formation from endosome-like structures at the synapse. Given the importance of this topic, future advances in this active field are expected to contribute to better comprehension of neurotransmission, and to have general implications for neuroscience and medicine.